Investigating environmentally friendly behavior among users and visitors of a Greek ski resort - Kontogianni, Evangelia; Kouthouris, Charilaos (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. Due to its climatic dependence ski industry is one of industries most visibly affected by the threat of environmental degradation and climate change. The present study aimed to investigate environmentally friendly behavior at a Greek ski resort. Specifically, the study aimed to investigate: a) attitudes towards environmental issues, b) verbal commitment to environmental actions, c) preferences for environmentally friendly services, d) willingness to pay more for environmentally friendly services, and e) demographic differences in terms of attitudes towards environmental services among users of a ski resort. Material and Methods. Two-hundred and fifty-five individuals (recreational skiers – 64.6%, snowboarders – 17.9%, resort visitors – 17.5%) completed a questionnaire consisting of four scales: Attitudes, Verbal commitment, Preference for environmentally friendly services and Willingness to pay more. Results. Results indicated strong positive correlations between variables (p < 0.01). As regards demographic characteristics statistically significant differences were found only between males and females on the ‘Attitudes towards environmental issues’ (p < 0.05) scale, with female users scoring higher(M = 5.53, SD = 0.59) than male users (M = 5.34, SD = 0.70). An analysis of variance between the three types of users revealed statistically significant differences on the ‘Verbal commitment to environmental actions’ (p < 0.01), and ‘Willingness to pay more’ (p < 0.01) scales. The subgroup of skiers scored significantly higher on both scales than the other two subgroups of ski resort users. Conclusions. The managerial and marketing implications of the study results are discussed. It is notable that differences in environmental issues are mainly between different types of ski resort users and not due to their demographic characteristics
Keywords: environment; attitudes; verbal commitment; eco-friendly preference; willingness to pay more; recreational skiing